Exploring the biological stability situation of a full scale water distribution system in south China by three biological stability evaluation methods. (October 2016) - Zhang, Junpeng; Li, Wei-Ying; Wang, Feng; Qian, Lin; Xu, Chen; Liu, Yao; Qi, Wanqi
Abstract: Bacterial regrowth especially opportunistic pathogens regrowth and contamination in drinking water distribution systems (DWDS) have become an emerging threat to public health in the whole world. To explore bacterial regrowth and biological stability, assimilable organic carbon (AOC), biodegradable dissolved organic carbon (BDOC) and bacterial regrowth potential (BRP) were evaluated in a full scale DWDS and bench tests in South China. A significant correlation between BRP and AOC in both water treatment processes (WTP) and DWDS was obtained. For BRP and BDOC, the correlation was more significant in WTP than in DWDS. Both AOC and BRP were significantly correlated with UV254, total organic carbon (TOC), and heterotrophic plate count (HPC) ( p < 0.01), whereas BDOC was only significantly associated with UV254, temperature and chlorine residual ( p < 0.01). Through a bench test, when chlorine was higher than 0.5 mg/L, the HPC level was low and AOC concentration almost unchanged. On contrary the HPC level increased quickly and declined slightly, with chlorine lower than 0.15 mg/L, which was in accordance with the large amount of biological stability data obtained from DWDS. Through another bench test, the HPC level was positively correlated to AOC concentration and when AOC was below 135 μg/L, the growth rate of HPC was low, which was verified by the analysis of biological stability data from DWDS. Highlights: Correlation between BRP and AOC was significant in either WTP or DWDS. Correlation between BRP and BDOC was more significant in WTP than in DWDS. High chlorine residuals largely suppressed bacterial regrowth in DWDS. Low chlorine residuals led to a positive correlation between AOC/BRP and HPC. Heterotrophic bacteria were limited compared to that when AOC was more than 135 μg/L.